Mara Capone (2024). Dal piano alla superficie Strumenti e metodi per costruire forme complesse. Milano: Franco Angeli (diségno, 2026)
The book Dal piano alla superficie. strumenti e metodi per costruire forme complesse by Mara Capone presents itself as an articulated, in-depth work capable of tracing a coherent trajectory that connects the conception, representation, and transformation of geometric forms. [read more]